"This kid looks like he has everything": 3‐ to 11‐year‐old children's concerns for fairness and social preferences when peers differ in social class and race. Issue 5 (25th April 2022) - Elenbaas, Laura; Luken Raz, Katherine; Ackerman, Amanda; Kneeskern, Ellen
Abstract: This study investigated 3‐ to 11‐year‐old US children's ( N  = 348) perceptions of access to resources, social group preferences, and resource distribution decisions and reasoning when hypothetical peers differed in social class (poor or rich) and race (Black or White). Data were collected in 2019. The sample reflected the region where data were collected in terms of gender (44% girls, 30% boys, 1% another identity) and race and ethnicity (46% White, 10% multiracial or multiethnic, 9% Black, 5% Latinx, 2% Asian, 3% another identity), and parents reported a higher average level of education than the regional average. Results revealed both marked age differences in children's perceptions, preferences, decisions, and reasoning and specific combinations of peer group memberships that were especially likely to receive preferential treatment. With age, children perceived that rich peers had greater access to resources than poor peers, but when both peers were poor, White peers were perceived to have more resources than Black peers. Social group preferences changed with age, from mixed social class and racial group preferences, to preferences for rich peers, to dislike for rich peers. Resource allocation decisions and reasoning reflected both social group and fairness concerns: young children distributed more to White peers especially if they were also rich, participants in middle childhood explicitly favored rich peers regardless of their race, and older children distributed more to poor peers and reasoned about either moral concerns for equity or social class stereotypes. Thus, overall, younger children's responses often reflected broader economic and racial inequalities while older children often sought to create more equity, though not always for moral reasons.